El eco-poema de Juan L. Ortiz - Forns-broggi, Roberto (Anales de Literatura Hispanoamericana, 2004)
Juan L. Ortiz is considered one of the major Argentine poets of the 20th century. The article proposes to introduce the reader to this singular poetic work that interlinks a spiritual perspective, the poetic voice and the natural landscape in a political and historical conscience alternative to the official discourses. Our first reading approach concentrates on the linguistic strategies that permit the fusion of these divergent worlds in the poem as an excess of transparency and of lightness. Ortiz manages to express with subtlety and ambiguity the life of the river landscape in the northeastern Argentine, and also to give form to a utopia that seeks harmony and continuity in change without ignoring pain and social injustice. The ecopoem works as an internal map of that landscape and its form of dialogue as a stream of questions that avoid fixed definitions. Another approach to the ecopoem originates from the evolving ethics of the landscape in which the ecological conscience is based as well as from a radical humanism. The type of utopia presented by the ecopoem requires not only an intersubjective space open to questioning and to ecological awareness, but also a reading that coincides with a methodological irregularity and is able to face the critical challenges of an alternative discourse.